Rancang Bangun Panel Ats (Automatic Transfer Switch) Sebagai Listrik Alternatif Pada Sumber PLN - Sri Widiastuti (Jurnal Ilmiah Wahana Pendidikan, 2023)
Electrical panel with the function of controlling 2 sources of electricity which can be handled automatically and safely of course. This ATS generator panel is actually suitable for use in factories, offices or hospitals that want a security system when moving the main source of electricity to an alternative power source. The working process of the ATS - AMF Panel Device is in principle if the electricity from the PLN is cut off, the ATS panel will immediately transfer the flow to the generator and the AMF will immediately turn on the generator automatically and distribute electricity and vice versa if the PLN electricity is on then it will automatically switch to PLN electricity. With the design above, it is shown that the main source enters ATS via the incoming from main/PLN terminal and the backup source enters ATS via the incoming from generator terminal. Meanwhile, supply to the load from ATS is connected to the outgoing terminal. To connect the load to the source, a three-phase 10 A/18 kA MCCB component is used and the contactor. Meanwhile, the generator contactor (K5 and K4 as Genset source connectors) will not be active, because before being connected to the generator contactor coil terminal, the control cable is connected to the auxiliary contact of the NC main contactor (PLN). Meanwhile, when the load is connected to a backup source (generator), the active contactor is the generator contactor. As with the first condition, the main contactor will not be active because before it is connected to the PLN coil terminal, the control cable is connected to the auxiliary contact of the generator contactor NC.